THE EFFECT OF GOVERNMENT INTERVENTIONS ON SHARE RETURN DURING THE COVID-19 PANDEMIC IN INDONESIA - Rayzi Maulizhar; Ririen Setiati Riyanti (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
This study aims to identify and analyze the impact of the announcement of the government's social distancing measures on stock returns and the impact of the announcement of the government's detention and health care policies on stock returns. This study uses a causal associative research strategy (cause and effect) quantitative approach. The population in the study used government response data using the Covid-19 Stringency Index. The Covid-19 variable uses data on the number of vaccinations in Indonesia. The stock return variable is obtained from the Composite Stock Price Index on the IDX (Indonesian Stock Exchange) with a sample period of 02 March 2020 to 31 December 2021. The analytical tool used is Eviews 10. Based on the analysis and discussion, it can be concluded that the announcement of the government's social distancing measures (government response) has a positive effect on stock returns and the impact of the announcement of government health care and detention policies (Health Index) has a positive effect on stock returns.